2016
DOI: 10.1088/1741-2560/13/6/066020
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of intracortical recordings using perforated and arrayed Parylene sheath electrodes

Abstract: The PSEA demonstrates the scalability of sheath electrode technology and provides higher electrode count and density to access a greater volume for recording. This study provided support for the importance of creating a supportive biological environment around the probes to promote the long-term electrophysiological performance of flexible probes in the cerebral cortex. In particular, we demonstrated beneficial effects of the Matrigel coating and the long-term expression of Caveolin-1. Furthermore, we provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…Thin parylene films are desirable packaging materials because they are hydrophobic barrier layers, present limited intrinsic biological activity, offer robust dielectric properties, and preserve mechanical flexibility (Loeb et al, 1977). Despite the relatively large hydraulic permeability of parylene compared to many inorganic films, flexible neural probes encapsulated in parylene-C achieve stable in vivo recordings for 12 months or longer (Hara et al, 2016). Nanoscale diamond is another emerging class of packaging materials (Narayan et al, 2011).…”
Section: Trends In Materials For Flexible Barrier Layersmentioning
confidence: 99%
“…Thin parylene films are desirable packaging materials because they are hydrophobic barrier layers, present limited intrinsic biological activity, offer robust dielectric properties, and preserve mechanical flexibility (Loeb et al, 1977). Despite the relatively large hydraulic permeability of parylene compared to many inorganic films, flexible neural probes encapsulated in parylene-C achieve stable in vivo recordings for 12 months or longer (Hara et al, 2016). Nanoscale diamond is another emerging class of packaging materials (Narayan et al, 2011).…”
Section: Trends In Materials For Flexible Barrier Layersmentioning
confidence: 99%
“…For example, an autoclave creates a high temperature and high humidity environment for sterilization, which can cause Parylene bilayers to delaminate and Parylene coatings to lose adhesion [ 57 , 91 ]. Alternative methods, such as the use of ethylene oxide, have been used successfully without damage to thin-film Parylene devices [ 36 ]. Several methods for sterilizing Parylene devices are described in literature and a brief summary of various methods and the major conclusions drawn regarding the effect on Parylene, is compiled in Table 2 .…”
Section: Challengesmentioning
confidence: 99%
“…Other devices include neurocages for in vitro neural network study [ 26 , 27 , 28 ], bellows for drug delivery [ 29 , 30 , 31 ], an electrochemical patency sensor [ 32 ], microfluidic devices [ 7 ] and electrothermal valves [ 33 ]. In the field of neural prostheses Parylene was used to create both penetrating ( Figure 3 c) [ 34 , 35 , 36 , 37 , 38 , 39 ] and non-penetrating microelectrode arrays [ 40 , 41 , 42 ]. Microfluidic channels were integrated into Parylene neural probes to inject drugs [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of soft polymer-based devices, while the former has been the subject of numerous studies [11,12,13,3], the latter remains little known. The mechanisms leading to changes in the properties of biomedical polymers are considered part of biodegradation mechanisms aecting its longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Some involve short-term implantation, between 3 weeks [19] and 5 weeks [20,21]. Recently, studies by Ellis Meng and coworkers showed proof of electrical recordings in rats for a period of 3 to 12 months, and primary investigation was carried out over signal quality [11], as well as immunohistochemical analysis [12]. But overall, if Parylene C is largely being investigated as a substrate for chronically-implanted neural probes, the stability of Parylene-based devices lacks crucial perspective.…”
Section: Introductionmentioning
confidence: 99%